The Development of an Islamic-based English textbook for third Grade Elementary Students - Zainuddin , Zainuddin (Universitas Islam Zainul Hasan Genggong, 2024)
The development of textbooks is one of the main factors in successful learning. This Islamic-based English textbook has the distinctive characteristics of contextual and Islamic-based material which is equipped with 4 aspects of language skills. This research aims to develop an Islamic-based English textbook and examine the validity and attractiveness of the textbook being developed. The research method used is research and development using the Borg & Gall design. The results of this research show that the development of English textbooks has good qualifications, as evidenced by the results of validation by material experts with a percentage of 80%, design experts with a percentage of 92%, and class teachers with a percentage of 94%. Textbooks have a high level of attractiveness as evidenced by the results of interviews and questionnaires with students with a percentage of 90.04%, so textbooks have fulfilled aspects of development & needs in the learning implementation process.